The Priority of Infrastructure Development in Kabupaten Lampung Barat - Ryansyah Izhar; Isye Susana; Sri Maryati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2018)
Infrastructure development is one of the important and vital aspect in order to accelerating the process of regional development. Infrastructure is also give an impact in improving the economy, accessibility, community development and the quality of human life. But, infrastructure development can’t be done simultaneously. Kabupaten Lampung Barat was designated by government as disadvantaged areas because of the lack on providing the infrastructure. Therefore, by using the analytical hierarchy process (AHP) this study is trying to find out the most important factor that affect the infrastructure development and the order of priority development of the five infrastructure in Kabupaten Lampung Barat, the infrastructure is: Roads, Drainage, Waste, Waste Water, and transportation. The AHP method revealed that the funding factor with the weight values 0,361, is the most important indicator that affect the infrastructure development in the study area. While, for the infrastructure, the AHP method revealed that roads infrastructure with weight values 0, 42, is the infrastructure which should be prioritized. Based on these result, the priority development of infrastructure in Kabupaten Lampung Barat is the provision of road infrastructure by increasing the capacity of the road and other road several indicators such as mobility and safety aspects